Synthesis and Characterization of Flexible Butadien Containing Resin for 3D SLA Printers - AKIN, EMRE; ÇAKIR, MUSTAFA (My University, 2022)
As well known, epoxy acrylate resins have been widely used in 3D SLA printers applications. Epoxy acrylate system consisted of bisphenol-A glycerolate diacrylate (epoxy acrylate resin) and 1,6-Hexanediol diacrylate (HDDA, reactive diluent resin) were used in this study. The weight ratio of epoxy acrylate and HDDA was determined as 1/1. The purpose of this study is to develop a novel epoxy acrylate system for 3D SLA printers and observe its properties. For this reason, a novel urethane acrylate was synthesized as reactive resin and was added into epoxy acrylate system with various weight percents. In order to obtain this novel urethane acrylate resin, hydroxyl terminated butadien oligomer was used as backbone of the chain while isophorone diisocyanate (IPDI) and 2-Hydroxyethyl methacrylate (HEMA) were used for synthesizing urethane acrylate functional groups. The addition of this novel reactive resin was carried out up to 1.5 %. Mechanical and physical tests were applied to the produced samples such as tensile, Shore-D hardness, abrasive and density tests. Considering of the results, substantial increases were observed in terms of tensile modulus. As expected, tensile strain values presented large decreases. Shore-D hardness and densities presented slight increases. Moreover, taber abrasive resistances of the produced novel samples presented considerable increases.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)